2015
DOI: 10.1111/myc.12302
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Sporothrix schenckii isolates from cats in Malaysia

Abstract: Epidemiological data on the aetiologic agents of feline sporotrichosis in Malaysia have not been reported, though human sporotrichosis in Malaysia is reported to be transmitted primarily via cat scratch. To the best of our knowledge, the present report is the first study of the molecular epidemiology of Sporothrix schenckii isolates from cats with sporotrichosis in Malaysia. In the present work, we characterised 18 clinical isolates from cats in Malaysia based on molecular properties, including sequence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…It is also the first time that antifungal susceptibility Based on our results, similar to what has previously been described, we confirmed that the feline Sporothrix isolates are of the species S. schenckii sensu stricto of a single clonal strain. 7 The majority of the isolates were thermosensitive, with a minority (18%) having the potential ability for lymphatic spread.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is also the first time that antifungal susceptibility Based on our results, similar to what has previously been described, we confirmed that the feline Sporothrix isolates are of the species S. schenckii sensu stricto of a single clonal strain. 7 The majority of the isolates were thermosensitive, with a minority (18%) having the potential ability for lymphatic spread.…”
Section: Discussionmentioning
confidence: 98%
“…Samples were inoculated on Sabouraud's dextrose agar containing 0.1 mg/mL of chloramphenicol (Oxoid; Hampshire, England) and stored at room temperature. Each isolate was then identified based on its morphological characteristics on culture, and on sequence analyses of its calmodulin gene and rDNA Internal Transcribed Spacer (ITS) region …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until a new TB vaccine is developed, M. bovis bacille Calmette-Guérin (BCG) remains the only effective vaccine for TB (6,7). BCG's overall efficacy, including cost-effectiveness, has been questioned by studies that were confounded by the cross-reactivity of antigens and the absence of measures to exclude latent infection before vaccination.…”
Section: Need For Bcg Vaccination To Prevent Tb In High-incidence Coumentioning
confidence: 99%